2022
DOI: 10.1038/s41598-022-18966-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic gains of some quantitative characters in Egyptian cotton cross (Giza 86 × Menoufi) under water deficit stress

Abstract: This work was carried out to select cotton genotypes adapted to semi-arid climate conditions cultivated under irrigation for high yields and the standards of the fiber quality properties required by the textile industry. Also to determine the predicted and realized gains from different selection indices to improve some economic characters under water stress conditions. Except for lint percentage and Pressley index, F4 generation reduced PCV and GCV values for all studied characters due to reduction in genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…(2016) showed that organic soil amendments stimulate antagonistic activities of microorganisms to soil-borne diseases and decomposition of organic matter in the soil, which resulted in bioactive antifungal or nematicidal compounds accumulation in the soil. Soils treated with a high level of organic matter reduced the Fusarium rot root index, and improved yields occurred ( Naseri, 2014 ; El-Saadony et al, 2021a ; Abd El-Aty et al, 2022b ; El-Ashry et al, 2022 ; El-Marzoky et al, 2022 ; El-Okkiah et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…(2016) showed that organic soil amendments stimulate antagonistic activities of microorganisms to soil-borne diseases and decomposition of organic matter in the soil, which resulted in bioactive antifungal or nematicidal compounds accumulation in the soil. Soils treated with a high level of organic matter reduced the Fusarium rot root index, and improved yields occurred ( Naseri, 2014 ; El-Saadony et al, 2021a ; Abd El-Aty et al, 2022b ; El-Ashry et al, 2022 ; El-Marzoky et al, 2022 ; El-Okkiah et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…Water scarcity is considered a natural phenomenon and is typically characterized as time without significant rainfall. It is the most significant constraint for rice production in rainfed habitats (Nelson et al, 2014;Pandey and Shukla, 2015;Abd El-Aty et al, 2022b). For instance, it causes considerable crop damage and a yield loss of more than 70% compared with normal conditions (Vaghefi et al, 2011;Abd El-Aty et al, 2022c;Abd El-Aty et al, 2022d).…”
Section: Introductionmentioning
confidence: 99%